Near-death experiences, attacks by family members, and absence of health care in their home countries affect the quality of life of refugee women in Germany: a multi-region, cross-sectional, gender-sensitive study - Jenny Jesuthasan; Ekin Sönmez; Ingar Abels; Christine Kurmeyer; Jana Gutermann; Renate Kimbel; Antje Krüger; Guenter Niklewski; Kneginja Richter; Ulrich Stangier; Anja Wollny; Ulrike Zier; et al. (BMC Medicine, 2018)
Abstract Background The year 2016 has marked the highest number of displaced people worldwide on record. A large number of these refugees are women, yet little is known about their specific situation and the hurdles they have to face during their journey. Herein, we investigated whether sociodemographic characteristics and traumatic experiences in the home country and during the flight affected the quality of life of refugee women arriving in Germany in 2015–2016. Methods Six hundred sixty-three women from six countries (Afghanistan, Syria, Iran, Iraq, Somalia, and Eritrea) living in shared reception facilities in five distinct German regions were interviewed by native speakers using a structured questionnaire. Sociodemographic data and information about reasons for fleeing, traumatic experiences, symptoms, quality of life, and expectations towards their future were elicited. All information was stored in a central database in Berlin. Descriptive analyses, correlations, and multivariate analyses were performed. Results The most frequent reasons cited for fleeing were war, terror, and threat to one’s life or the life of a family member. Eighty-seven percent of women resorted to smugglers to make the journey to Europe, and this significantly correlated to residence in a war zone (odds ratio (OR) = 2.5, 95% confidence interval (CI) = 1.4–4.6, p = 0.003) and homelessness prior to fleeing (OR = 2.1, 95% CI = 1–4.3, p = 0.04). Overall the described quality of life by the women was moderate (overall mean = 3.23, range of 1–5) and slightly worse than that of European populations (overall mean = 3.68, p < 0.0001). The main reasons correlating with lower quality of life were older age, having had a near-death experience, having been attacked by a family member, and absence of health care in case of illness. Conclusions Refugee women experience multiple traumatic experiences before and/or during their journey, some of which are gender-specific. These experiences affect the quality of life in their current country of residence and might impact their integration. We encourage the early investigation of these traumatic experiences to rapidly identify women at higher risk and to improve health care for somatic and mental illness.